Kontrol Diri dan Impulsive Buying Remaja (Studi Pada Pengguna Tiktokshop) - Khairiyah, Miftahul (Jurnal Humanipreneur, 2023)
Impulsive buying is a person's behavior when they buy something without planning or spontaneously. This research uses quantitative methods to explain the role of self-control on impulsive buying in teenagers through Tiktokshop media. The sample in this study amounted to 154 respondents, the sampling technique used was purposive sampling and snowball sampling. The measuring instrument used in this research uses two variables, namely self-control compiled by Tangney et al., the purchasing section compiled by Verplanken & Herabadi (2001). The research results show that there is a negative and significant influence of self-control on impulsive buying among teenage TikTok users, and vice versa. Self-control plays a role in impulse buying by 2.7%.